Raised Blood Pressure as a Risk Factor of Post-Operative Seroma Formation in Patients of Modified Radical Mastectomy - Muhammad Ayyub Anjum, Muhammad Ahmed Naseer, Ahmad Rafique, Bashir Ahmad Noor, Jamal Abdul Nasir, Amina Rasheed (Pakistan Journal of Medical & Health Sciences, 2022)
Despite seroma is rarely potentially lethal and is typically harmless, it can cause considerable sequelae such as flap necrosis, wound dehiscence, predisposes to infection. The objective of the study was to determine the association of raised blood pressure as a risk factor of development of seroma after MRM in breast cancer patients. Material Methods: In this case control study, all women of age 30 to 70 years with MRM done for carcinoma of the breast of stage T2 and lymph nodes N2 were enrolled and followed for 3 days after MRM surgery for seroma formation. Out of total 122 patients, 64 patients were cases and 58 controls. Patients with disease upto N2 had level 2 clearances with upfront surgery. Age, history of essential hypertension, compression bandage applied, serum albumin level, seroma formation and volume of seroma on 3rd post-operative day was documented. Results: Mean age of the patients was 51.2 + 9.5 years and 53.5 + 10.8 years in case and control, respectively. Majority of the patients were of the age group 40 to 50 year’s age group. 56.3% (n=36) cases and 43.8% (n= 28) controls had history of essential hypertension. Seroma formation was seen in cases 51% (n=31) as compare to controls 13% (n= 8) with odd ratio OR 1.48. Drainage volume among two groups was analyzed as in case group, the drainage volume was 148.1 + 76.4 ml (range 50 to 290) while in control group the drainage volume was 130 + 56.9 ml (60 to 250) and was statistically significant with p-value <0.001. Conclusion: Although the pathogenesis of seroma remains controversial, hypertension is the most consistent significant risk factor for seroma formation subsequent to modified radical mastectomy for carcinoma breast. Good pre, peri and post-operative blood pressure control can reduce the risk of seroma formation and the associated morbidity. Keywords: MRM, Seroma, nodal clearance, breast cancer,